Equality Reflected at This Earth of Mankind Novel By Pramoedya Ananta Toer (1975): A Marxist Approach - Fachrullah, Rivaldi, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2015)
This research paper is proposed to analyze the equality in novel entitled This Earth of Mankind using Marsist Approach. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the novel based on the Marxist approach. This research is descriptive qualitative research. There are two kinds of Data sources in this research, namely the primary and the secondary data sources. The primary data source is This Earth of Mankind novel written by Pramoedya Ananta Toer and translated by Max Lane. Meanwhile the secondary data sources are materials other sources such as books, dictionary, internet and journal which is related to the study. The techniques of data collection in this research are summarizing, paraphrasing, and documenting the data and this study is analyzed using descriptive analysis. Based on the analysis, the researcher draws the following conclusions. First, based on the structural elements, it shows that the character and characterization, setting plot, theme, point of view, and style create unity which are connected each other and makes this novel interested to be read. Second, based on Marxist analysis, the author reflects the social reality of Indonesian society during Dutch colonialism period. Trough this novel, the author presents the inequality and equality which is achieved by Natives in Dutch colonialism. Keywords: Equality, This Earth of Mankind, Marxist Approach.